The influence of leadership style and personality towards organizational commitment at PT. Pupuk Sriwidjaja Palembang in Indonesia - Saputra, Andri Jutawan (2014)
Organizational commitment plays pivotal role for a company to acquire the loyalty of its employs. Organizations with greater loyalty of their employees turn such potential resources into their goal with more efficiency. On the other hand, organizations will suffer from low performance on account of high turnover, absenteeism, less motivation and job withdrawal behavior. Hence, both leadership style and personality may become major determinants to organizational commitment. In addition, the stereotype of gender is considered to be exogenous variable to determine the impact of both leadership style and personality on organizational commitment. This research aims to determine the influence of leadership style and personality on organizational commitment. To answer the research questions, this study uses quantitative method with a set of questionnaires adapted from literatures. The survey was conducted in Indonesia industrial scenario, specifically at PT Pupuk Sriwidjaja Palembang (PUSRI). The questionnaires were distributed to 300 employees with random sampling approach, then 285 respondents contributes to this study. Data analysis uses multistage least square with SPSS. Overall, the study provides evident that both leadership style and personality of the managers have significant effect on organizational commitment. This shows that a great managerial personality integrates with strong leadership styles may generate better commitment among employees within the observed organization. This study give extend contribution to the theory which explains the impact of both leadership style and personality on organizational commitment by considering the gender perspective.